Strategic Visits in The Field of Pharmacy, Challenges and Opportunities - Chini, Reyhaneh; Pourebtehaj, Ali; Bagheri, Sara; Mostafavipoor, Seyed Mehrdad; Barzegar, Alireza; Mohagheghzade, Abdolali (International Pharmacy Acta, 2018)
Introduction: Regarding the needs of pharmacy field to targeted planning, strategic and field visits with objective preconditioning approach is one of the effective methods for preparing students for strategic planning. Methods and Results: In this study, first, the papers were reviewed since1993to2016.Then opportunities and challenges such as the importance of strategic visits to education and research, the pharmacist’s future job, the content of the visit, the achievements, and the place and time of the visit were assessed by Likert questionnaire contains 20questions and through google form for 2categories of students. The first group included students who had experiences of visiting during the travel conducted by the Strategic Studies Center; and second group included the students who did not have experience of Strategic Visits. Conclusions: In the first group with 20 people as statistical population, 90% agreed to the role of the visits in increasing the ability and creating educational and research attitudes, 70.4% opposed with the feeling of disappointment and confusion by visiting, 85% agreed to motivate and acquaint with job opportunities. In addition, 95% agreed to visit the policy-making centers, 100% agreed to visit the industry and university, and 30% agreed to visit cultural centers. 60% agreed to pass 2related syllabuses before visiting the relevant center, 45% agreed with the requirement of mentioned cases, and 65% agreed to make the visit in the elementary courses of education. These obtained results for the second group with 130 people as statistical population were 87.1%, 67.8%, 96.8%, 93.5%, 48.4%, 93.5%, 19.4%, 67.8%, 58.1% and 58.4%, respectively.